1990
DOI: 10.1177/000841749005700410
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting a Clinician's Decision to Provide Fieldwork Education to Students

Abstract: Fieldwork represents an important component of the education of an occupational therapist. In this study thirteen occupational therapists in small Saskatchewan occupational therapy facilities were interviewed to determine the factors and the relationships among these factors that affected their involvement in the fieldwork process. The directors of the two large occupational therapy departments in Saskatchewan, together with eight Canadian university fieldwork coordinators were interviewed for comparison purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
22
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 14 publications
9
22
1
1
Order By: Relevance
“…Across all supervisory levels, more respondents perceived challenges to accepting students than not. A lack of time was the most frequently identified barrier to accepting level II fieldwork students, consistent with prior research (Tompson & Proctor, 1990). Perceiving a lack of time, however, did not appear to be an obstacle to accepting fieldwork students as previous research might suggest.…”
Section: What Are the Current Barriers Perceived By Mental Health Occsupporting
confidence: 83%
See 2 more Smart Citations
“…Across all supervisory levels, more respondents perceived challenges to accepting students than not. A lack of time was the most frequently identified barrier to accepting level II fieldwork students, consistent with prior research (Tompson & Proctor, 1990). Perceiving a lack of time, however, did not appear to be an obstacle to accepting fieldwork students as previous research might suggest.…”
Section: What Are the Current Barriers Perceived By Mental Health Occsupporting
confidence: 83%
“…This was interesting when contrasted with the finding that "Perceives Lack of Time" failed to be associated with student numbers. Apparently, time limitations as suggested by Tompson and Proctor (1990) are a clinical reality for the present sample; however, this perception did not appear to make a difference in terms of commitment to fieldwork education. Rather, perceiving no challenges to offering a fieldwork placement was the more crucial variable in support of clinical education.…”
Section: What Factors Predict Student Numbers In Level I and Level Iicontrasting
confidence: 52%
See 1 more Smart Citation
“…However, the gift becomes more of a commodity when it is embedded in professional structures that emphasize professional and moral responsibilities, synonymous with 'obligation' and 'duty' (Blanchard Edwards 1969). The principle of supporting the profession by becoming a practice-educator-mentor is an example of an assumed professional obligation that is identified in occupational therapy (Tompson & Procter 1990), medicine (General Medical Council 2013), physiotherapy (Chartered Society of Physiotherapy 2011) and nursing (Nursing and Midwifery Council, 2008). Martinez-Aleman's (2007, p578) suggestion that "gift exchange might not be consonant with the spirit of obligation or contractual exchange" but rather that "gifts move because they are social bonds between self and other" is of concern in the current climate in health and social care.…”
Section: Duty and Obligationmentioning
confidence: 99%
“…The constraints of limited time and increased workload are ongoing fieldwork concerns (Canadian Association of Occupational Therapists, 1990; Thompson and Proctor, 1990;Green, 1996). Nevertheless, Paterson (1997) found that clinicians' productivity increased with the presence of a student.…”
Section: Literature Reviewmentioning
confidence: 99%